Adaptive model for thermal comfort of students in secondary schools in the tropical city of Makassar - Hamzah, Baharuddin; Mulyadi, Rosady; Ishak, Muhammad Taufik (AIP Conference Proceedings, 2022)
This research aimed to examine the thermal comfort performance of students in naturally ventilated secondary schools’ classrooms in Makassar. The analysis compared the thermal balance and the adaptive model. The study analyzed data gathered from surveys conducted at eight secondary schools and local weather stations. The data consists of the measured indoor thermal environment of 48 classrooms. The personal data, users’ perceptions, and adaptive behaviors of 1,594 students were recorded in the questionnaire sheets. The questionnaire also recorded the thermal perception of students about the thermal environments of classrooms. In terms of thermal sensation, the study found that the neutral temperature estimated by PMV was overestimated the neutral temperature developed by actual votes of students. The PMV model estimated the neutral temperature of students at 23.0 °C which was about 7 °C lower than the neutral temperature calculated using the students’ actual thermal sensation votes (30.2 °C). This was a very big discrepancy between the predicted and the actual. The adaptive thermal comfort model produces more appropriate results than the PMV model. The modified Humphrey’s model predicted more close neutral temperature to the actual one which was 29.1 °C. Students adapt to the thermal environment through several activities. This adaptation makes students remain comfortable even in the hot thermal environment.
Keywords: _C:Indonesia; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:keyword:thermal comfort; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education

A review on windcatcher for passive cooling and natural ventilation in buildings, Part 1: Indoor air quality and thermal comfort assessment - Jomehzadeh, Fatemeh; Nejat, Payam; Calautit, John Kaiser; Yusof, Mohd Badruddin Mohd; Zaki, Sheikh Ahmad; Hughes, Ben Richard; Yazid, Muhammad Noor Afiq Witri Muhammad (Renewable and Sustainable Energy Reviews, 2017)
The most prominent challenge in 21th century is global warming which seriously threats the mankind. Building sector with 40% of global energy consumption and GHG emission play a key role in this threat. In this regard, the impact of cooling systems cannot be ignored where along with ventilation and heating systems totally account for 60% of energy consumed in buildings. Passive cooling systems can be a promising alternative to reduce energy consumption. One of the oldest passive cooling system that is still being used today is windcatcher. By manipulating pressure differences and the buoyancy effect, an adequate level of ventilation in buildings can be provided by windcatchers. Since most of the previous windcatcher studies assessed the design characteristics, the current investigation focused on the indoor air quality (IAQ) and thermal comfort aspects. The review details and compares the different theoretical and experimental methods employed by researchers in different case studies to assess the IAQ and thermal comfort. It was found that most IAQ studies were conducted in the UK using CFD and experimental techniques. Previous studies assessed IAQ based on several parameters such as air flow rate, air change rate, CO2 concentration, air change effectiveness and mean age of air. The findings of the studies revealed that satisfactory IAQ were generally achieved using the windcatcher. On the other hand, thermal comfort studies of windcatchers were mainly conducted in hot climates such as in the Middle East. In addition to night ventilation, the review also looked into the different types of cooling methods incorporated with windcatchers such as evaporative cooling, earth to air heat exchangers (EAHE) and heat transfer devices (HTD). Night ventilation was found to be effective in temperate and cold conditions while additional cooling using evaporative cooling, EAHE and HTD were found to be necessary in hot climates.
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indoor air quality; oa:keyword:natural ventilation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T13298 Solar Chimney Systems; openalex:n:1; openalex:yes

An investigation of thermal comfort in classrooms in the tropical Savanna climate - Mustapha, Tajudeen Dele; Hassan, Ahmad Sanusi; Nasir, Muhammad Hafeez Abdul; Onubi, Hilary Omatule (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:keyword:tropical savanna climate; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T12950 Learning Environments in Education; thermal sensation

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes